High-performance extruded Mg89Y4Zn2Li5 alloy with deformed LPSO structures plus fine dynamical recrystallized grains. (15th November 2016) - Liu, Wei; Zhang, Jinshan; Xu, Chunxiang; Zong, Ximei; Hao, Jianqiang; Li, Yi; Zhang, Zhe
Abstract: The effects of the Li addition on the microstructure evolution of Mg94-x Y4 Zn2 Lix (at.%, x = 0, 1, 5, 9 and 13) alloys were systematically investigated. Little Li (< 1 at.%) addition facilitated the formation of 18R LPSO phases, but exceeded Li (> 1 at.%) addition inhibited the precipitation of 18R LPSO phases. While the (Mg, Zn)24 Y5 eutectic phases increased gradually with the addition of Li. Microstructural refinement was significant when the content of Li was 5 at.%. Li addition also changed the formation behavior of 14H LPSO phase of solid-solution Mg89 Y4 Zn2 Li5 alloy only containing α-Mg and LPSO phases. The ultimate tensile strength and elongation of as-extruded Mg89 Y4 Zn2 Li5 alloy reached to 385 MPa and 14%, respectively. The coexistence of kinky block 18R LPSO phases and fine dynamical recrystallized (DRXed) grains surrounding bent lamellar 14H LPSO phases was responsible for the excellent mechanical properties. Graphical abstract: Highlights: Effects of the Li addition on long period stacking ordered structures were investigated. Extrusion speed and die angle should be emphatically considered. High strength and ductility Mg89 Y4 Zn2 Li5 alloy was obtained. Excellent performance due to deformed long period stacking ordered structures and fine dynamical recrystallized grains.